Efficacy of rinsing chlorhexidine digluconate 0.12% and povidone iodine 1% on total bacterial count as aseptic technique at Department of Oral Surgery, Faculty of Dentistry, Universitas Sumatera Utara - Isnandar; Hendry Rusdy; Indra B. Siregar; Karisha HS. Ashari (Journal of Dentomaxillofacial Science, 2021)
Objective: To compare chlorhexidine digluconate 0.12% and povidone iodine 1% on total bacterial count after mouth rinsing at the department of oral surgery, Faculty of Dentistry, University of Sumatera Utara Material and Methods: This was an experimental study with post-test only control group design approach. Purposive technique was applied to collect samples which are clinical students. In this study, sample were divided into 3 groups and each consisting of 12 people. Normal saline 0.9% was used as control group while chlorhexidine digluconate 0.12% and povidone iodine 1% was used as the treatment group. Each member performed mouth rinsing for 30 seconds. Results: The results were statistically analyzed using Kruskal Wallis and Mann-Whitney test. The comparison between chlorhexidine digluconate 0.12% and povidone iodine 1% showed a significant difference to the total bacteria count after mouth rinsing (p<0.05) and the chlorhexidine digluconate 0.12% group showed a greater mean reduction. Conclusion: Chlorhexidine digluconate 0.12% reduce more bacteria than povidone iodine 1%. However, both of the antiseptic agents can be a choice for mouth rinsing.